Superconducting penetration depth in amorphous metals - Arce, R.; de la Cruz, F.; Esquinazi, P. (Elsevier, 1981)
Fil: Arce, R. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina